Elderly satisfaction with the Public Health Service: an integrative literature review (Research, Society and Development, 2020)
The article evaluates the satisfaction of the elderly about the quality of the Brazilian Public Health Service, based on an integrative literature review study, which gathers information published between 2011 and 2018, about this group the perception of related to the service provided by the health care network. This consists of five stages: guiding question elaboration, literature search, critical data analysis, data integration and presentation of results. It was consulted SciElo, LILACS and Capes Periodicals databases, with the following descriptors: "elderly", "user satisfaction", "health service evaluation" and "primary health care". After selecting the studies, 14 articles were used to structure this integrative review. It is noticed that a good part of the elderly population feels satisfied with the service that is offered by most institutions in the public health network. However, controversies are observed in studies, since some presented a positive evaluation in several aspects cited by the elderly, such as, the care and guidance provided by professionals, while others, exhibit these same indicators considered serious weaknesses, such as ease of access to these services. Therefore, the satisfaction of the elderly with the public health service was noted, among which the assistance and guidance of the different professionals were the best evaluated indicators by the respondents.